The comparative assessment of capillary and venous Babesia rossi parasitaemias on thin blood smears and their association with disease manifestation - Schoeman, Johan P. (University of Pretoria, 2013)
Dissertation (Master of Veterinary Medicine (Small Animal Medicine))--University of Pretoria, 2006.